Design of bacterial polyester beads for recombinant protein production, biomolecule separation and detection : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Philosophy in Microbiology at Massey University, Palmerston North, New Zealand - Du, Jinping (Massey University, 2018)
Protein recovery and biomolecule detection are commonly required for scientific research as well as industrial activities. However, it is generally complicated and costly either to produce and purify recombinant proteins (especially therapeutic proteins) from engineered 𝘌𝘴𝘤𝘩𝘦𝘳𝘪𝘤𝘩𝘪𝘢 𝘤𝘰𝘭𝘪 cells, or to directly separate proteins or detect other biomolecules from natural sources. Here the PHA synthase (PhaC) mediated polyhydroxyalkanoate (PHA) bead display technology was explored as a solution to these problems by developing streamlined processes with less complex steps to achieve protein recovery and biomolecule detection. Firstly, by fusing a target protein to PhaC via a self-cleavable linker tag of either sortase (sortase A from 𝘚𝘵𝘢𝘱𝘩𝘺𝘭𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘢𝘶𝘳𝘦𝘶𝘴) or intein (DnaB mini intein from 𝘚𝘺𝘯𝘦𝘤𝘩𝘰𝘤𝘺𝘴𝘵𝘪𝘴 𝘴𝘱. PCC 6803), new self-cleavable recombinant protein production and purification resins were developed. It was shown that the PhaC fusion could mediate 𝘪𝘯 𝘷𝘪𝘷𝘰 production of PHA beads displaying the target protein. Functional target protein could be obtained at high purity from isolated PHA beads by incubation with CaCl2 and triglycine (in the case of the self-cleavable sortase tag) or by a pH shift to 6 (in the case of the self-cleavable intein tag). Six recombinant proteins were successfully produced and purified via the intein approach, including 3 model proteins (𝘈𝘦𝘲𝘶𝘰𝘳𝘦𝘢 𝘷𝘪𝘤𝘵𝘰𝘳𝘪𝘢 green fluorescent protein (GFP), 𝘔𝘺𝘤𝘰𝘣𝘢𝘤𝘵𝘦𝘳𝘪𝘶𝘮 𝘵𝘶𝘣𝘦𝘳𝘤𝘶𝘭𝘰𝘴𝘪𝘴 vaccine candidate Rv1626, and the synthetic immunoglobulin G (IgG) binding ZZ domain of protein A derived from 𝘚𝘵𝘢𝘱𝘩𝘺𝘭𝘰𝘤𝘰𝘤𝘤𝘶𝘴 𝘢𝘶𝘳𝘦𝘶𝘴) and 3 therapeutic proteins (human tumour necrosis factor alpha (TNFα), human interferon alpha-2b (IFNα2b), and human granulocyte colony-stimulating factor (G-CSF)). Of these, TNFα and IFNα2b were also successfully produced and purified via the sortase approach. Secondly, 𝘪𝘯 𝘷𝘪𝘷𝘰 one-step production of PHA affinity resins was achieved by fusing to PhaC differently customised OBody ligands. These ligands were previously engineered by other groups from the OB-fold domain of aspartyl-tRNA synthetase (aspRS) from 𝘗𝘺𝘳𝘰𝘣𝘢𝘤𝘵𝘶𝘭𝘶𝘮 𝘢𝘦𝘳𝘰𝘱𝘩𝘪𝘭𝘶𝘮, by using phage display technology, to have specific binding affinities to biomolecules of interest. The resulting recombinant OBody beads were used for lysozyme sepration from a complex substrate, and for progesterone (P4) binding. Further optimisation of the P4 binding condition is necessary before the OBody bead system can be used for P4 detection in bovine milk. However, recombinant immobilisation of OBody ligands on the surface of PHA beads expands not only the attractiveness of these emerging OBody scaffolds, but also the utility scope of PHA beads as affinity resins.
Keywords: Biopolymers; Recombinant proteins; Recombinant proteins; Purification; Biomolecules; Separation